2011
DOI: 10.1370/afm.1279
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Health Records vs Medicaid Claims: Completeness of Diabetes Preventive Care Data in Community Health Centers

Abstract: PURPOSE Electronic Health Record (EHR) databases in community health centers (CHCs) present new opportunities for quality improvement, comparative effectiveness, and health policy research. We aimed (1) to create individual-level linkages between EHR data from a network of CHCs and Medicaid claims from 2005 through 2007; (2) to examine congruence between these data sources; and (3) to identify sociodemographic characteristics associated with documentation of services in one data set vs the other. METHODSWe stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 48 publications
2
67
0
Order By: Relevance
“…A study particularly highlighted the benefit of electronic medical record (EMR) data over claims data [13]. This resulted in the recent development of databases that combine both claims data and EMR data for health care analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A study particularly highlighted the benefit of electronic medical record (EMR) data over claims data [13]. This resulted in the recent development of databases that combine both claims data and EMR data for health care analysis.…”
Section: Discussionmentioning
confidence: 99%
“…DeVoe et al have found that, in a network of Community Health Centers, EHR data provide a more comprehensive picture of preventive services delivery than Medicaid claims data. 4 These fi ndings add to the argument that EHRs can be important tools for research, policy, and reimbursement, particularly when pertaining to the under-and uninsured.…”
Section: High Tech Low Techmentioning
confidence: 95%
“…Devoe, et al [7] compared the entries in EHRs with the same data in the Medicaid claims data set for a group of 50 community health centers in Oregon. They found gaps in data congruence across the study group, with some services documented in the Medicaid data set but not the EHRs, and others documented in the EHRs but not in the Medicaid data set.…”
Section: Background and Literaturementioning
confidence: 99%
“…The primary effort was the development of a set of data governance and data life cycle processes that focused on the awareness of data quality. 7 The studies in other industries point to the processes deployed and potential for change relevant to the health care industry, while the studies of health services data frame some of the known challenges and complexities that remain in the health care industry. For many community health centers, which serve especially vulnerable populations, and tend to be less well-resourced than hospital providers, understanding the complexities related to data collection and use, and developing appropriate strategies to improve data collection and use information more effectively, remain challenging.…”
Section: Background and Literaturementioning
confidence: 99%